Simulation of Self- Rechargeable Electric Vehicle - Muhammad Buhari, Sheih; Azliza, Nur; ., Sivakumar (International Journal of Engineering and Technology, 2019)
This paper proposed the self-rechargeable electric vehicle by using â€œCrocodile Clipâ€ simulation. A proposed self-recharge is to recharge the battery by the rotation of the wheel and it drives the motor during generator mode. On this mode, the motor be able to produce current because the motor act as a generator. On motor mode, the system helps in increasing speed of the vehicle. The mode is switchable to the driver needs. The purpose of this paper is to overcome the problem of lack of charging station availability in the country. This paper allows the user to charge the vehicle on the go. In this paper, two motors has been designed, namely all-time motor and switchable motor. During motor mode, both motor will be rotating and it makes the vehicle travel in higher speed. Meanwhile in the generator mode maintains the speed at 13rpm.. In conclusion, the battery is allowed to be charged during generation mode and circuit itself will run the motor during motor mode.Â Â Â
Keywords: Self-rechargeable electric vehicle; switchable motor to generator; generator mode; motor mode.